Change management in multicultural organisations - Parkes, Aneta (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
This article presents some of the change management tools, which can be useful especially in the environment of multicultural organisations, to manage the process of change. At the beginning of the article the change management and multicultural organisations will be defined. Then the change management process will be characterised and the chosen tools of change management will be described. The choice of these tools is based on personal work experience and interviews with change leaders who have been managing changes in multicultural organisations.